A Panel Data Analysis of Earnings Growth Determinants in Jakarta Islamic Index - Sholahuddin, Muhammad; Jannah, Zainur Miftakhul; Kussudyarsana, K; Achmad, Nur (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to analyze the influence of current ratio, and total asset turnover on profit growth. Current ratio is one of liquidity ratio and total asset turnover is one of activity ratio. This type of research is quantitative data. The population used in this study is all companies registered in the Jakarta Islamic Index (JII) period 2016-2020. This research hypothesis test uses secondary data with purposive sampling techniques and companies that meet the criteria of 18 companies. Secondary data uses data collection by means of documentation. The analysis methods used are Multiple regression test of panel data, Classic assumption test, goodness of fit model accuracy test and hypothesis testing. The results of this study partially show that the current ratio has a significant positive effect on profit growth. While total asset turnover negatively affects profit growth. Simultaneously the current ratio and total asset turnover have a significant effect simultaneously on the company's profit growth.